The Effectiveness of Twitter as a Literacy Medium in Improving College Students' Reading and Writing skills: - Idawati Situmorang; Hamela Sari Sitompul; Mery Chris Isabela Saragih (Jurnal Mantik, 2022)
Mastery of English is a must and the demands of the times because English is an international language. Therefore, college students are expected to be able to use digital media such as social media Twitter as a means of accessing information in increasing motivation and knowledge in English. So far, college students only use the Twitter application as a lifestyle. In fact, Twitter can be used as a learning resource that can increase college students' learning motivation and English skills because Twitter has features that are more relaxed and more interesting. This study aims to analyze the effectiveness of Twitter as a literacy medium in improving college students' reading and writing skills. This research is a descriptive analysis research using a quantitative approach. This study uses an experimental method without a comparison class because all college students were taught using the Twitter application. In this study there were 20 college students as the sample. The results showed that the use of Twitter can improve college students' reading and writing skills. In reading skill, the average score of pre-test was 68 and post-test was 85.5. The average score of writing skill in the pre-test was 56.5 and the post-test score was 78. It can be concluded that there was an increase in the college students' reading and writing skill test scores.